602Prevalence of cancer history and association with risk factors in a healthy older population. (2nd September 2021) - Orchard, Suzanne; Lockery, Jessica; Gibbs, Peter; Polehkina, Galina; Wolfe, Rory; Zalcberg, John; Haydon, Andrew; McNeil, John; Nelson, Mark; Reid, Christopher; Kirpach, Brenda; Murray, Anne; et al.
Abstract: Background: The ASPirin in Reducing Events in the Elderly (ASPREE) study randomised healthy older individuals to 100mg aspirin or placebo, with clinical outcomes and disability-free survival endpoints. Detailed baseline data provides a rare opportunity to explore cancer burden and association with known cancer risk factors in this population. Methods: At enrolment (2010-2014), self-reported personal cancer history, cancer type and cancer risk factor data were sought from 19, 114 participants (Australia, n = 16, 703; U.S., n = 2, 411). Participants were healthy and expected to survive 5 years. Results: Of those reporting a prior cancer diagnosis (18% women, 22% men), women were diagnosed younger (16% vs 6% of diagnoses <50 years). Cancer prevalence increased with age. Prostate and breast cancer history were higher in U.S. participants; melanoma and colorectal cancer were higher in Australian participants. Cancer history prevalence was not associated with any common risk factors, but was associated with poor health ratings in men. Blood and breast cancer history was more common with past aspirin use. Conclusions: Personal cancer history in healthy older ASPREE participants was as expected for the most common cancer types in the respective populations. The lack of alignment with known risk factors is attributable to survivor bias, driven by entry criteria, and to possible molecular differences in cancer between elderly and younger people. Key messages: As the prevalence of cancer increases with age, the lack of alignment with known risk factors implies other factors play a significant role.